Activity of β-lactam/taniborbactam (VNRX-5133) combinations against carbapenem-resistant Gram-negative bacteria. (9th October 2020) - Mushtaq, Shazad; Vickers, Anna; Doumith, Michel; Ellington, Matthew J; Woodford, Neil; Livermore, David M
Abstract: Background: Boronates are of growing interest as β-lactamase inhibitors. The only marketed analogue, vaborbactam, principally targets KPC carbapenemases, but taniborbactam (VNRX-5133, Venatorx) has a broader spectrum. Methods: MICs of cefepime and meropenem were determined combined with taniborbactam or avibactam for carbapenem-resistant UK isolates. β-Lactamase genes and porin alterations were sought by PCR or sequencing. Results: Taniborbactam potentiated partner β-lactams against: (i) Enterobacterales with KPC, other class A, OXA-48-like, VIM and NDM (not IMP) carbapenemases; and (ii) Enterobacterales inferred to have combinations of ESBL or AmpC activity and impermeability. Potentiation of cefepime (the partner for clinical development) by taniborbactam was slightly weaker than by avibactam for Enterobacterales with KPC or OXA-48-like carbapenemases, but MICs of cefepime/taniborbactam were similar to those of ceftazidime/avibactam, and the spectrum was wider. MICs of cefepime/taniborbactam nonetheless remained >8 + 4 mg/L for 22%–32% of NDM-producing Enterobacterales. Correlates of raised cefepime/taniborbactam MICs among these NDM Enterobacterales were a cefepime MIC >128 mg/L, particular STs and, for Escherichia coli only: (i) the particular bla NDM variant (even though published data suggest all variants are inhibited similarly); (ii) inserts in PBP3; and (iii) raised aztreonam/avibactam MICs. Little or no potentiation of cefepime or meropenem was seen for Pseudomonas aeruginosa and Acinetobacter baumannii with MBLs, probably reflecting slower uptake or stronger efflux. Potentiation of cefepime was seen for Stenotrophomonas maltophilia and Elizabethkingia meningoseptica, which have both chromosomal ESBLs and MBLs. Conclusions: Taniborbactam broadly reversed cefepime or meropenem non-susceptibility in Enterobacterales and, less reliably, in non-fermenters.